2010
DOI: 10.1111/j.1346-8138.2010.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against cyclic citrullinated peptide in Japanese psoriatic arthritis patients

Abstract: Anti-cyclic citrullinated peptide antibodies (anti-CCP) are highly considered to indicate disease severity and be predictive markers in rheumatoid arthritis (RA). RA patients who are positive for anti-CCP tend to progress more frequently to joint deformity and functionally deteriorate more than negative patients. A study concerning the presence of anti-CCP in Japanese patients with psoriatic arthritis (PsA) has been published. Our aim was to clarify that anti-CCP could be a potentially useful marker in PsA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…While these antibody responses were previously thought to be nearly unique to RA, 43 several recent clinical trials have revealed the presence of anticyclic citrullinated peptide (anti‐CCP) in patients with psoriatic arthritis (PsA), with a prevalence ranging between 5·6% and 15·7% 44 . The presence of anti‐CCP in PsA has been demonstrated to be significantly associated with the HLA‐DRB1 shared epitope, a marker of disease severity, as well as with RA‐linked major histocompatibility complex class II, prompting the authors of two investigations to purport that the presence of anti‐CCP in patients with PsA may indicate that they will develop severe joint disease, 44,45 with a third paper directly suggesting that anti‐CCP antibodies are potential indicators of severity and predictive markers in patients with PsA 41 . Although the mechanism underlying the association remains unclear, one possibility is that anti‐CCP plays a role in sustaining the inflammatory response 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these antibody responses were previously thought to be nearly unique to RA, 43 several recent clinical trials have revealed the presence of anticyclic citrullinated peptide (anti‐CCP) in patients with psoriatic arthritis (PsA), with a prevalence ranging between 5·6% and 15·7% 44 . The presence of anti‐CCP in PsA has been demonstrated to be significantly associated with the HLA‐DRB1 shared epitope, a marker of disease severity, as well as with RA‐linked major histocompatibility complex class II, prompting the authors of two investigations to purport that the presence of anti‐CCP in patients with PsA may indicate that they will develop severe joint disease, 44,45 with a third paper directly suggesting that anti‐CCP antibodies are potential indicators of severity and predictive markers in patients with PsA 41 . Although the mechanism underlying the association remains unclear, one possibility is that anti‐CCP plays a role in sustaining the inflammatory response 44 …”
Section: Discussionmentioning
confidence: 99%
“…41 Although the mechanism underlying the association remains unclear, one possibility is that anti-CCP plays a role in sustaining the inflammatory response. 44 Another connection involving P. gingivalis is its activation of Th17-inducing pathways. Patients with CP have been shown to have an increased expression of interleukin-17, with these increased levels having been demonstrated to correlate with increased tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the presence of antibodies against the protease inhibitor calpastatin, anti‐stratum corneum antibodies, antithyroid microsomal antibodies, antinuclear antibodies and anti‐dsDNA antibodies in Ps patients, and concluded that latent autoimmune disease may develop in Ps patients, without any clinical symptoms resulting from the formation of these antibodies . The presence of the anti‐cyclic citrullinated peptide antibody has also been demonstrated in patients with Ps and PsA . However, no specific autoantibody was identified to be characteristic of all patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate that keratinocyte hyperproliferation triggered by skin‐infiltrating T cells plays an important role in the formation of psoriatic lesions . A few reports have also demonstrated autoantibody production including antinuclear, anti‐dsDNA and antithyroid microsomal antibodies …”
Section: Introductionmentioning
confidence: 99%
“…Another aspect that warrants further investigation is the clinical utility of the anti-CCP antibody test in HIV-associated inflammatory arthritis, particularly in reactive arthritis and psoriatic arthritis subtypes. There is mounting evidence of an increased prevalence of anti-CCP antibodies in idiopathic psoriatic arthritis and some early evidence that their presence is associated with more aggressive disease 13 .…”
Section: The Scourge Of Hiv Infection In Sub-saharan Africa -A Rheumamentioning
confidence: 99%